METHODOLOGY OF THE AUDIT OF ENVIRONMENTAL MANAGEMENT OF THE WETLANDSOF PERÚ WTHIN THE FRAMEWORK OF THE RAMSAR CONVENTION - Mogrovejo Espinoza, Martín Edmundo (2012)
The study formulates how the technical/operative alignments of the Ramsar Convention facilitate the implementation of the environmental and audit management methodology of the wetlands of Peru. It’s an investigation on an explanatory level, developed in a sample of five wetlands: Reserva Nacional de Paracas (Ica), Refugio de Vida Silvestre Los Pantanos de Villa (Lima), Santuario Nacional Lagunas de Mejia (Arequipa), Santuario Nacional Manglares de Tumbes (Tumbes) y Reserva Nacional Junín ( Junín and Pasco). The research instruments used were: The Interview of civil employees responsible for the wetlands, the information Card of the Ramsar wetlands, and the list of verifications. We conclude that the application of the methodology of the audit of environmental management for the specific case of the wetlands of Peru must be framed in the alignments of the protocol of monitoring of the Ramsar Convention, which its application is inescapable of the exigencies of the convention.